Genetic variation in tree leaf chemistry predicts the abundance and activity of autotrophic soil microorganisms. Issue 8 (1st August 2019) - Selmants, Paul C.; Schweitzer, Jennifer A.; Adair, Karen L.; Holeski, Liza M.; Lindroth, Richard L.; Hart, Stephen C.; Whitham, Thomas G.
Abstract: Genetic variation in the chemistry of plant leaves can have ecosystem‐level consequences. Here, we address the hypothesis that genetic variation in foliar condensed tannins along a Populus hybridization gradient influences soil ammonia oxidizers, a group of autotrophic microorganisms that perform the first step of nitrification and are not dependent on carbon derived from plant photosynthesis. Evidence that genetically based plant traits influence the abundance and activity of autotrophic soil microbes would greatly expand the concept of extended plant phenotypes. We found that increasing foliar condensed tannin concentration reduced rates of soil nitrification potential by ~75%, reduced the abundance of ammonia‐oxidizing archaea by ~66%, but had no effect on ammonia‐oxidizing bacteria. Other indices that often drive nitrification rates, including soil total nitrogen, foliar nitrogen, and soil pH, were not significant predictors of either the activity or the abundance of ammonia oxidizers, suggesting genetic variation in foliar condensed tannins may be the dominant regulating factor. These results demonstrate the condensed tannin phenotypes of two different tree species and their naturally occurring hybrids have extended effects on a key ecosystem process and provide evidence for indirect genetic linkages among autotrophs across at least two domains of life.